Intermittent exercise alleviates MI-induced renal injury in mice via IGF-1 - Zhu, Wanyu; Bo, Wenyan; Ma, Yixuan (Frontiers in Physiology, 2025)
Myocardial infarction (MI) often induces acute kidney injury (AKI) via systemic hypoperfusion and oxidative stress, yet the protective mechanisms of exercise remain unclear. This study investigated whether intermittent exercise alleviates MI-induced AKI through the insulin-like growth factor-1 (IGF-1)/PI3K/AKT signaling pathway. An AKI model was established in mice via coronary artery ligation, followed by moderate-intensity intermittent treadmill training for 4 weeks. Echocardiography, serum biochemical markers, renal histology, RT-qPCR, and Western blotting were used to assess cardiac and renal function, inflammatory cytokines, oxidative stress, apoptosis, and IGF-1/PI3K/AKT signaling. In vitro, H2O2-treated NRK renal cells were used to mimic oxidative damage. Recombinant human IGF-1 (rhIGF-1), AMPK agonist AICAR, IGF-1 receptor inhibitor NVP-AEW541, and PI3K inhibitor LY294002 were applied to explore the pathway’s involvement in exercise-induced renoprotection. MI led to impaired cardiac function, renal structural injury, elevated BUN and MDA levels, increased expression of IL-6, TNF-α, Bax, and Cleaved Caspase-3, and decreased SOD activity. Intermittent exercise improved cardiac output, attenuated renal injury, enhanced antioxidant capacity, and upregulated IGF-1 expression and its downstream PI3K/AKT signaling. In vitro, rhIGF-1 and AICAR mimicked the protective effects of exercise, while IGF-1R or PI3K inhibitors partially abolished these effects. These findings suggest that intermittent exercise ameliorates MI-induced AKI by activating the IGF-1/PI3K/AKT pathway, thereby exerting anti-inflammatory, antioxidant, and anti-apoptotic effects. This study highlights the role of exercise-induced IGF-1 in heart-kidney axis protection and provides a mechanistic basis for therapeutic interventions targeting MI-related renal complications.